Ambition of the Main Character in Quintessence Novel by Jess Redman - Unpris Yastanti; Anggraini; Izzah, Nadila Nurul; Rohati, Titi Dewi (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2022)
The purpose of this research are to find features of ambitious people, discover kinds of Murray’s human needs, and analyze factors that determine ambition-level of the main character. Therefore, to seek the result, Quintessence novel by Jess Redman is chosen in this research. This study uses the descriptive qualitative method to investigate the data. The data were gathered by reading the novel, examining passages, collecting important parts and explaining the result. The result of this research reveals; (1) 13 features of ambitious people in the main character there are personal interest, willing to connect, strong desire, problem solving, confidence, motive others, hardworking, risk taker, maximize capability, emotion stability, self-development, critical thinking, and kind-hearted person, (2) in total, 17 kinds of human needs are catered when the main character pursuing her ambition goal there are conversance, order, construction, achievement, infavoidance, defendance, conteraction, dominance, deference, similance, autonomy, blameavoidance, affilation, succorance, nurturance, cognizance, exposition and (3) some factors determine ambition-level of main character are located such as prior experience, purpose of ambition, group influence and realism.